Title: Metacognitive Strategies for EFL Writing - Nemouchi, Oualid (Journal of Human Sciences, 2017)
Throughout the years, educators have long been confronted with the predicament of how to teach their students and how to make them responsible for their own learning. Scholars have proposed various probable solutions to the previously underlined dilemma. One such highly influential suggestion, proposed by researchers, is the establishment of a teaching philosophy that takes into consideration the students’ social, intellectual, physical, mental, and emotional needs. As far as language learning is concerned, instructors must bridge the gap between psychology, linguistics, and cognition. Within the auspices of the latter, metacognition is thought of as an indispensable pillar which serves the purpose of clarifying critical issues related to how students learn, how they know what they have learnt, and how to direct their own future learning.